Cabling and interfaces for Karoo Array telescopes : modelling and metrology - Van der Merwe, Paul Stephanus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.